Effects of gamma-ray irradiation on electronic and non-electronic equipment of Large Helical Device. (3rd January 2017) - Ogawa, K; Nishitani, T; Isobe, M; Sato, M; Yokota, M; Hayashi, H; Kobuchi, T; Nishimura, T
Abstract: In a deuterium operation on the Large Helical Device, the measurement and control equipment placed in the torus hall must survive under an environment of  radiation. To study the effects of gamma-ray irradiation on the equipment, an irradiation experiment is performed at the Cobalt-60 irradiation facility of Nagoya University. Transient and permanent effects on a personal computer, media converters, programmable logic controllers, isolation amplifiers, a web camera, optical flow meters, and water sealing gaskets are experimentally surveyed. Transient noise appears on the web camera. Offset of the signal increases with an increase of the integrated dose on the programmable logic controller. The DeviceNet module on the programmable logic controller is broken at the integrated dose of 72 Gy, which is the expected range of the integrated dose of the torus hall. The other equipment can survive under the gamma-ray field in the torus hall.